Value and Growth Investing in Asian Stock Markets: 1991-2002 - KANG, Joseph (Institutional Knowledge at Singapore Management University, 2005)
The study discussed in this article examines two empirical questions: (1) Can multiple financial signals enhance the intermediate-horizon returns of value and glamour investments on Asian stock markets? and (2) Do the return enhancements, if any, differ by value and growth firm types and vary across different markets? The results of this study show that financial signals affect return enhancements, and these enhancements differ by firm types and vary across markets. These differences can be explained by non-positive value premiums and relatively poor information quality documented on Asian markets.